Modeling and querying alternative paths in Kuantan - Mohamad Salleh, Mazlina (2007)
Route finding based on geodetic data had addressed the growing data management and analysis needs of spatial applications such as Geographic Information System (GIS). Spatial databases are prominently used in Geographic Information System (GIS) application like digital map application. This study discusses the process of modeling data from map on road network information consisting of points including the starting and ending road points and intersection between other road segments. It enables the storage of spatial dataset or the geographical information syatem (GIS) for calculation of distance between points. Route finding solution takes the distance information in the form of directed graph based on starting (source) and ending (destination) nodes for the desired paths. The graph theory algorithm used in this study is applied from the Floyd’s approach and using the combination of searching techniques of breadth first search (BFS) and depth first search (DFS) strategies. The structured query language (SQL) is used for querying the database structures. A browser interface for the system makes the information dissemination easier.